Can Habits Impede Creativity by Inducing Fixation? - Ibáñez de Aldecoa, Paula; de Wit, Sanne; Tebbich, Sabine (Frontiers in Psychology, 2021)
In a competitive and ever-changing world, the ability to generate outstanding ideas is crucial. However, this process can be impeded by factors such as fixation on ideas that emerged through prior experience. The aim of the present study was to shed light on the fixating effect of habits on creativity. To this end, healthy young adults were asked to generate alternative uses for items that differed in their frequency of use in the Alternative Uses Task (a standardized test for divergent thinking). We predicted that frequent past use of an item would lead to the formation of stimulus-response associations between the item and its most frequent use(s) and thereby hinder idea generation. Indeed, individuals were less flexible (but more fluent) in generating ideas for frequently used items than for unknown items. Additionally, we found that subjective automaticity of idea generation was negatively related with flexibility. Finally, we investigated whether individual differences in general habit tendency influence creativity, by relating performance on the Slips-of-Action task (an outcome devaluation paradigm extensively used in habit research) to performance on the Alternative Uses Task, the Candle Problem (a classic convergent thinking task) and two puzzles (non-conventional problem-solving tasks). While we did not find a significant relationship between habit tendency and the Alternative Uses Task or the Candle Problem scores, the tendency to rely on habits predicted probability to succeed and latency to solve one of the puzzles: less habit-prone participants were more likely to solve it and to do so faster. In conclusion, our study provides evidence for the notion that habits can negatively impact creativity and opens promising future avenues of research in this field.